A general structural equation model of the emotions and repurchase intention in modern retail - Simanjuntak, Megawati; Rachmawati Nur, Hanum; Sartono, Bagus; Sabri, Mohamad Fazli (Growing Science, 2020)
The major objective of this study is to analyze the effect of the shopping environment and situation as perceived by modern retail shoppers into perceived crowding, store image, and shopping motives toward emotions and repurchase intention in the context of a grocery modern retail. The cross-sectional design method was used in this study, and the data were collected from a customer survey with randomly selected 244 respondents using an online questionnaire. According to the findings the perceived crowding, store image, and shopping motives affected positively on the customer emotions. The perceived crowding was revealed as the most influential variable on the emotions. We also found a direct effect of perceived crowding and store image on repurchase intention. Furthermore, the high-density retail condition shoppers tend to feel pleased with the shopping environment and give a positive appraisal to the store image. But unfortunately, a high-density retail condition could discourage the shoppers to have repurchase intention. Interestingly, when the emotions were used as a mediating variable of perceived crowding and repurchase intention, those independent variables affected on repurchase intention, positively. Therefore, the shoppers' emotions were the most important factor affected on repurchase intention in modern retail. The more they enjoy the shopping environment and situations, the more they are interested in making future purchases.